Potassium indole-3-butyric acid affects rice’s adaptability to salt stress by regulating carbon metabolism, transcription factor genes expression, and biosynthesis of secondary metabolites - Zhou, Hang; Meng, Fengyan; Jiang, Wenxin; Lu, Xutong; Zhang, Rui; Huang, Anqi; Wu, Kunlun; Deng, Peng; Wang, Yaxin; Zhao, Huimin; Du, Youwei; Huo, Jingxin; et al. (Frontiers in Plant Science, 2024)
Soil salinity pollution is increasing worldwide, seriously affecting plant growth and crop production. Existing reports on how IBAK regulates rice salt stress adaptation by affecting rice carbon metabolism, TF gene expression, and biosynthesis of secondary metabolites still have limitations. In this study, 40 mg•L -1 IBAK solution was sprayed on rice leaves at the seedling stage. The results showed that the IBAK application could promote shoot and root growth, decrease sucrose and fructose content, increase starch content, and enhance AI and NI activity, indicating altered carbon allocation.Furthermore, the expression of TF genes belonging to the ERF, WRKY, and bHLH families was influenced by IBAK. Many key genes (OsSSIIc, OsSHM1, and OsPPDKB) and metabolites (2-oxoglutaric acid, fumaric acid, and succinic acid) were up-regulated in the carbon metabolism pathway. In addition, this study highlighted the role of IBAK in regulating the biosynthesis of secondary metabolites pathway, potentially contributing to rice stress adaptability. The results of this study can provide new sustainable development solutions for agricultural production.